Comparison of the effects of spark plasma at two different voltages on aspects influencing skin rejuvenation - Erfan Ghasemi; Mohammad Ali Nilforoushzadeh; Mohammadreza Khani; Mohammad Amir Amirkhani; Maryam Nouri; Parisa Charipoor; Babak Shokri (PLoS ONE, 2025)
Skin is not only the body’s largest organ but also one of the most noticeable and hard-working parts. Every day, it shields us from things like bumps, changes in temperature, and harmful substances in the environment. But as we age, this protection starts to weaken. Spending too much time in the sun, being exposed to pollution, and other stressors lead to visible signs of aging, such as dry skin, uneven color, fine lines, and a loss of firmness and elasticity. Recently, spark plasma has shown great potential as a gentle and non-invasive way to help the skin heal itself. In earlier research [16], we studied how applying spark plasma at 3.44 kV affected the skin, and the results were very encouraging. Inspired by those findings, we continued with more research. In this study, we tested two different levels of spark plasma—3.44 kV and 4.88 kV—to see how each affected the skin in different ways. We measured changes in skin color, firmness, density, tightness, moisture, and thickness using both MPA9 biophysical tests and ultrasound imaging. We noticed that both levels led to visible improvements in the skin, but the higher voltage had a stronger effect, especially when it came to increasing collagen and speeding up the healing process. Interestingly, there was a brief increase in redness and melanin right after the treatments, but these effects went away and returned to normal within four weeks. Most importantly, there were no scars, long-term irritation, or harmful side effects during or after the treatments.